(untitled) (Filologia e Linguística Portuguesa, 2022)
This paper aims to discuss and investigate a relevant issue related to palaeographic literacy: the influence of writing history on contemporary texts, and the emergence of writing. The research was done with basis on well-known theorists in this field of studies: Fischer (1999, 2006), Martins (2002), Janson (2015); and others, who investigate writing nowadays: Soares (2002) and Street (2012). The study consisted of the analysis of two groups of texts: one group comprises texts produced in the eighteenth century, considering that they contain crucial features for the study at play. The other group consists of school texts selected from the internet. This assisted us to realize and comprehend how writing evolved over the years. Results proved that palaeography is not only a science that contributes to decoding ancient texts. It also plays an important role in practices of writing of contemporary texts. This proves that palaeography did not get stuck in its time. On the contrary, when it comes to writing, it is connected to every social movement which emerges over the years. We could notice that it is an interdisciplinar science, seeing that it makes a good contribution to Linguistics as a whole. To sum up, paleography does not only reflects the history of writing, but also helps in the processs of production and reception of contemporary texts. We can regard it as a science which advanced as other important sciences did in our society. We are opposed to some scholars who believe that palaeography got stuck in ancient times. Our findings in our research proved that it may treated as a modern science. Therefore, their rationale needs be re-thought.